Literature Review: Healthy Home as The New Normal for Covid19 Prevention - Fairuz Haniyah Ramadhani (Universitas Airlangga, 2020)
Introduction: The SARS-CoV-2 virus has 2 pathways of spread which are direct (through droplets) and indirect (through the surface of objects affected by droplets or through air). Therefore, social distancing by staying in home is one of the key to prevent the spread of Covid19. However, the transmission of SARS-CoV-2 is increasingly common in family level. The risk of family members getting infected is higher because they begin to move outside the house during new normal. Accordingly, a good home environment is needed to improve its residents' health. This study aims to determine the benefits of implementing healthy home as the new normal in preventing the spread of Covid19 at family level. Discussion: This study was a literature review using literature research as the data source. The literature used were in the form of research journals and articles on Covid19 and healthy home. The data used were research studies conducted from January 2016 to June 2020. There was 9 articles, about benefit healthy home on SARS-CoV-2 transmission, that selected in this study. Healthy home was the idea of homes that have fulfilled the health standards with adequate sanitation. Healthy home was purposively built to make the residents feel comfortable and stay healthy at all times. The components of healthy home were: good ventilation; natural lighting of the house; occupancy density; residents' behavior; and waste management. Conclusion: The application of healthy home principle had many benefits for its residents and was closely related to Covid19 prevention.